Pendidikan di Singapore: Keberhasilan Implementasi Kebijakan Pendidikan Berbasis Sistem Meritokrasi dan Pengembangan Guru - Haq, Ahmad Matinul; Sholeh, Muhammad (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2023)
Abstract: This research examines the successful implementation of meritocracy-based educational policies and the professional development of teachers in Singapore. The method used in this research is qualitative based on literature research by collecting information or data from trusted sources, such as journal articles and books. After that, it is analyzed in content, processed briefly and systematically. The research results show that the implementation of meritocracy-based education policies in Singapore has been successful in increasing the quality of learning in the country. This policy ensures that outstanding students are given appropriate recognition and incentives, thereby encouraging them to continue learning, being competitive, and performing high. Not only that, this policy also helps increase accountability and transparency in the learning system. The development of qualified teachers is also a major focus in Singapore's learning policy. Teachers in Singapore are given the opportunity to develop themselves reliably. Teachers are given the opportunity to take 100 hours per year for their professional development (Professional Development / PD). Thus producing a more efficient learning area. Overall, this research shows that meritocracy-based educational policies and teacher professional development in Singapore have been successful in increasing the quality of learning and producing better learning areas. This is what makes Singapore in its education zone very advanced and becomes a reference for other countries to study there, let alone try to imitate its policy system.Keywords: Singapore, Education Policy, Meritocracy, Teacher Development Abstrak: Riset ini mengulas tentang keberhasilan implementasi kebijakan pendidikan berbasis meritokrasi dan pengembangan profesional guru di Singapore. Metode yang digunakan dalam riset ini merupakan kulitatif yang berbasis riset pustaka dengan mengumpulkan informasi ataupun data dari sumber- sumber yang terpercaya, semacam artikel jurnal, serta buku- buku. Setelah itu di analisis secara isi, diolah secara ringkas serta sistematis. Hasil riset menampilkan kalau implementasi kebijakan pendidikan berbasis meritokrasi di Singapore sudah sukses tingkatkan mutu pembelajaran di negeri tersebut. Kebijakan ini membenarkan kalau siswa-siswi yang berprestasi diberikan pengakuan serta insentif yang pantas, sehingga mendesak mereka buat terus belajar, berkompetitif, serta berkinerja besar. Tidak hanya itu, kebijakan ini pula menopang tingkatkan akuntabilitas serta transparansi dalam sistem pembelajaran. Pengembangan handal guru pula jadi fokus utama dalam kebijakan pembelajaran Singapore. Guru di Singapore diberikan peluang buat meningkatkan dirinya secara handal. Guru di berikan peluang buat mengambil 100 jam per tahun buat pengembangan profesionalnya (Professional Development/ PD). Sehingga menghasilkan area belajar yang lebih efisien. Secara totalitas, riset ini menampilkan kalau kebijakan pendidikan berbasis meritokrasi dan pengembangan profesional guru di Singapore sudah sukses tingkatkan mutu pembelajaran serta menghasilkan area belajar yang lebih baik. Perihal tersebutlah menjadikan Singapore dalam zona pendidikannya sangat maju serta jadi referensi negara-negara lain buat belajar disitu apalagi mencoba meniru sistem kebijakannya.Kata kunci: Singapore, Kebijakan Pendidikan, Meritokrasi, Pengembangan Guru